The Mapping Science Learning in The 2013 Curriculum and Merdeka Belajar Curriculum - Dani Rahma Harfiani; Anatri Desstya (Jurnal Ilmiah Sekolah Dasar, 2023)
Basic education in Indonesia has experienced various curriculum developments, from the 2013 Curriculum to the Independent Learning Curriculum. However, from a transitional point of view, it still needs to provide a clear direction for some practitioners. This study aims to analyze the mapping of planning, to implement, and evaluating science learning in the 2013 Independent Learning Curriculum. Data collection techniques were carried out through interviews, observation, and documentation. The data validity test was carried out by source triangulation. The subjects of this study were the principal and teachers of class IV SD. Data analysis techniques performed interactive models: data reduction, presentation, and conclusion. The results of the study show that the teacher prepares the administration of the Science learning plan in the 2013 Curriculum, namely the syllabus, porta, promissory notes, preparation of lesson plans for Learning Implementation Plans (RPP), media, teaching materials, and evaluation, while in the Independent Learning Curriculum, the teacher prepares learning tools in the form of Learning Outcomes ( CP), Learning Objectives (TP), Learning Objective Flow (ATP), teaching modules, and evaluation. The implementation of science learning in the 2013 Curriculum uses integrated thematic learning supported by applying a scientific approach, while in the Merdeka Learning Curriculum, it is carried out based on products, processes, and attitudes. In evaluating science learning in the 2013 curriculum, teachers use the cognitive, psychomotor, and affective domains, while in the Merdeka Learning Curriculum, teachers use diagnostic assessments, formative assessments, summative assessments, and projects.